Transformations of welfare regimes in Colombia (2021)
The article shows the process of evolution of three referential models of social policy and welfare regime at the dawn of the XXI century in Colombia. The method of cognitive analysis in public policies is used as a strategy for the construction of data, evidence and arguments that allow describing and interpreting the various approaches and types of social policy implemented in territorial contexts characterized by an increase in relations of exclusion and inequality. The results show that the most developed approaches in Colombia are welfare, neo-welfare (social protection) and inclusive, views that have been building a form of minimal and hybrid welfare regime with difficulties to guarantee human rights and socio-territorial integration. The conclusions show the ambiguity of the approaches and the increase in intermediaries in the implementation of social policies at the local level.